Transformative partnerships for a food-secure world (March 2013) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Learning together transforms agriculture and lives. Narrated by food policy leader Lindiwe Majele Sibanda. Watch the new version of this video at: http://youtu.be/rWLvn1yQUbE For more information visit: https://ccafs.cgiar.org/blog/farmers-and-scientists-better-together-fight-against-climate-change